Gambaran Dampak Picky Eater pada Anak Usia Remaja - Yeni Setiani; Indra Tri Astuti; Herry Susanto (Journal of Health, Medical, and Psychological Studies, 2026)
Adolescence is a developmental phase characterized by significant physical, psychological, and social changes, including the formation of eating behavior. One phenomenon that commonly emerges is picky eating, defined as a tendency to select or reject certain types of food. This behavior may persist into adolescence and potentially affects psychological, physiological, and cognitive conditions. This study aims to describe the impact of picky eating among adolescents at SMA Kesatrian 1 Semarang. This study employed a survey design with a sample of 156 adolescents selected through purposive sampling. Data were collected using the Picky Eater Scale (PES), the DASS-42, BMI and hemoglobin measurements, and the Cognitive Assessment Questionnaire (CAQ). Data analysis was conducted using univariate analysis. He findings showed that 82 respondents (52.6%) were categorized as picky eaters. Psychological impacts were most commonly found in the severe category (25.6%). Physiological impacts were indicated by mild anemia in 45 respondents (28.8%) and below-normal BMI in 55 respondents (35.5%). The most frequent cognitive impact was in the low category, recorded in 59 respondents (37.8%). Picky eating affects the psychological, physiological, and cognitive conditions of adolescents. The psychological impact is mostly categorized as severe, the physiological impact is reflected in mild anemia and below-normal BMI, and the greatest impact appears in the cognitive aspect (37.8%), with most respondents classified in the low category.